Effectiveness of Carrot Juice and Ginger Brewing on Reducing Primary Menstrual Pain (Dysmenorrhea) in Adolescent Females in RW 33, Sako Village, Palembang City - Riska Widya Astuti; Ike Sri Wahyuni; Bulan Purnama Sari (CV. Get Press Indonesia, 2025)
Menstrual pain can have adverse effects it can cause psychological instability. menstrual pain can have adverse effects. One of the non-pharmacological treatments to overcome menstrual pain (dysmenorrhea) is carrot juice and ginger decoction. Objectives and Methods: To determine the effect of carrot juice and ginger decoction on reducing menstrual pain in adolescent girls in the RW 33 area of ​​Sako Village, Palembang City. The research design is an experimental time series design. The population is all adolescent girls with a total sampling of 20 respondents each in the carrot juice treatment group, ginger decoction and warm compress control group. Pain was assessed using pre-test and post-test scores on the Numerical Rating Scale (NRS), statistical analysis tests using the Wilcoxon test, Kruskall wallis and binary logistic regression. Results: There was a decrease in menstrual pain pre and post non-pharmacological treatment p-value 0.00 <0.05, the group that had the most influence on reducing menstrual pain was the ginger decoction group (p-value 0.028 <0.05). Conclusion: carrot juice and ginger decoction as an alternative to reduce menstrual pain (dysmenorrhea) in adolescent girls. However, ginger decoction is more effective than carrot juice and warm compresses.